Early-Life Infection in Cystic Fibrosis and Lung Disease Progression - Argyri Petrocheilou MD; Maria Papagrigoriou-Theodoridou MD; Athanasios Michos MD; Stavros-Eleftherios Doudounakis MD; Ioanna Loukou MD; Athanasios Kaditis MD (SAGE Publishing, 2017)
Lung disease in cystic fibrosis (CF) starts early, with studies identifying abnormalities on chest computed tomography (CT) scan even in infancy. In this retrospective study, abnormal chest CT was the main outcome; body mass index (BMI) z score and forced expiratory volume percent predicted (FEV 1 %) predicted at age 6 to 7 years were secondary outcomes. Pseudomonas aeruginosa infection prior to 12 months of age was the main explanatory variable. There was no association between early P aeruginosa infection and abnormal CT after adjustment for CFTR (cystic fibrosis transmembrane conductance regulator) functional mutation class, gender, and other pathogens (odds ratio = 0.30; 95% confidence interval = 0.07-1.35; P = .11). No significant associations were demonstrated for BMI z score and FEV 1 % predicted. Children with class I-III CFTR mutations had increased risk of abnormal CT findings (odds ratio = 11.67; 95% confidence interval = 1.11-115.06; P = .035) and lower FEV 1 % predicted ( P = .04). In the current era, early-life P aeruginosa infection in CF might not influence the severity of lung disease in school age as much as previously. Larger studies are needed to confirm this finding.